Bioinspired Sulfo oxygen bridges optimize interfacial water structure for enhanced hydrogen oxidation and evolution reactions - Chengdong Yang; Yun Gao; Zhengyu Xing; Xinxin Shu; Zechao Zhuang; Yueqing Wang; Yijuan Zheng; Shuang Li; Chong Cheng; Dingsheng Wang; Jintao Zhang (Nature Communications)
Abstract Uncovering the dynamic structures of water at the electrode-solution interface is crucial for various electrocatalysis processes, where water acts as a proton and electron source. However, precisely controlling the state of water on complex interfaces remains challenging. Inspired by the metalloproteins in natural enzymes, we herein demonstrate that the hydrophilic sulfo-oxygen bridging between Co and Ru sites (Cos-SO-Ru) optimizes interfacial water structure via a favorable hydrogen-bond network, promoting hydrogen oxidation and evolution reactions. Mechanistic studies reveal that the stereoscopic sulfo-oxygen bridges enhance the connectivity of hydrogen-bond network to promote the proton transfer process via repelling cations from the electrode surface. Furthermore, electron donating Co sites reduce the surface oxophilicity of Ru to optimize the adsorption-desorption behaviors of hydroxyl, governing the timely refreshed Ru sites to enhance catalytic performances. Such bioinspired active sites offer a different pathway for the precise design of interfacial water structure to improve electrocatalysis.